The Emergence of Justice Climate in Groups, Teams, and Organizations: A Theory of Multilevel Information Aggregation and Judgment - Rupp, D. (Institutional Knowledge at Singapore Management University, 2009)
We outline a theoretical model of the emergence of justice climate in groups, teams, and organizations, and in doing so integrate multiple justice perspectives (e.g., affective events, fairness heuristic, deonance, justice integration, multifoci justice, overall justice). We propose that justice climate is spawned at the event level, where individuals use their emotional reactions to situations as information in forming fairness judgments. Over time, these judgments about various perpetrators--which may include the evaluation of outcomes, procedures, information, and interpersonal treatment--are aggregated to form individual-level stable judgments regarding the fairness of exchange partners with whom employees interact (e.g., supervisors, co-workers, customers). Through socialization and social-information processing, and influenced by organizational structural and social networks, these individual multifoci justice perceptions merge to form (unit-level) shared cognitions of overall justice. The paper concludes with recommendations for empirically testing the model.